Painting Dublin, 1886-1949 : visualising a changing city - Milligan, Kathryn (Manchester University Press, 2020)
This book explores artists' visualisations of Dublin during a key period of the city's political and social history. Based on close and contextual readings of original paintings and prints, along with new archival research, it shows how artists in Ireland creatively responded to the urban environment where they lived and worked.